Building Secure Software - Mcgraw, [ MEI ] John Viega Gary.; Viega, John ([S.l.] : Machinery Industry Press, 2013)
Paperback. Pub Date :2014-03-01 Pages: 336 Language: Chinese Publisher: Machinery safety technology known as book publishers of the Yellow Emperor by the security forces to create a pro-technology guru. best-selling global. digital security technology experts jointly recommended. Comprehensive discussion on how to build a security barrier in the entire software development life cycle. software for the design of safety guidelines given farsighted. comprehensive and informative. easy to understand. For any concern about the safety of software development people. is an essential book. The book is divided into two parts. The first part introduces the code should know before writing software security knowledge on how to introduce security in software engineering practice. any person involved in software development should read. The main contents include: Introduction to the guidi...
Keywords: System design; Computer security; Development; Information technology; Security measures; Computer networks; Data protection; Computer software; Security measures